Young Australians: their health and wellbeing 2011 - AIHW; Australian Institue of Health and Welfare (AIHW, 2011)
This report is the fourth in a series of national statistical reports on young people aged 12-24 years, produced by the Australian Institute of Health and Welfare. It provides the latest available information on how Australia's young people are faring according to a set of national indicators of health and wellbeing. Death rates have fallen considerably among young people, mainly due to declines in injury deaths. Most young people are achieving national minimum standards for reading, writing and numeracy, are fully engaged in study or work, and have strong support networks. There are some favourable trends in risk and protective factors, such as declines in smoking and illicit substance use. But it is not all good news. There is a high rate of mental disorders among young people, and road transport accidents, although continuing to decline, are still a major cause of death among young males. Too many young people are overweight or obese, are not doing sufficient physical activity or eating enough fruit and vegetables, and are drinking alcohol at risky levels. Aboriginal and Torres Strait Islander young people are far more likely to be disadvantaged across a broad range of indicators.
AIHW Youth report statistical series
Keywords: Children -- Adolescents and youth; Children; Health -- Wellbeing; Health; Adolescents and youth; Health and wellbeing; Children; Health; Wellbeing; Adolescents and youth; Health and wellbeing; Adolescents and youth